Stitching together SNx units in the coordination sphere of zirconium: assembly of a tris(imido)sulfite and a hydrazidobis(imido)sulfite - Gehrmann, Thorsten; Kruck, Matthias; Wadepohl, Hubert; Gade, Lutz H. (Chemical communications, 2012)
Reaction of a zirconium imido and a hydrazinediido complex with bis(trimethylsilyl)sulfur diimide yielded the corresponding formal [2+2] cycloaddition products, the trisimidosulfito complex and the hydrazidobis(imido)sulfito complex containing an unprecedented SN2(N-N) unit.